Zielsetzung des Pressedienstes des Grenzschutzes. Analyse der Aktivitäten während der Migrationskrise an der polnisch-belarussischen Grenze - Soczyński, Sławomir; Teler, Anna (Przegląd Wschodnioeuropejski, 2025)
In the crisis on the Polish-Belarusian border context in 2021 attention was paid to the role of the Border Guard Spokesmen and the goals they pursue: informational, national security and image. A context-sensitive content analysis of the collected research material was carried out to obtain quantitative and qualitative results. It was found that the Border Guards Spokesmen’ statements to the media are primarily concerned with informing (~84%), and to a lesser extent pursues the national security goal (~37%) and image goal (~32%). The statements were observed to be set in context and relevant to current events. Depending on the situation on the border and the public discourse, the dynamics of the goals changed. The conclusions provided are intended to mobilize further discussion on the contemporary role and tasks of gatekeepers: not only journalists, but also state functionaries, and contribute to reflection on media discourse – its goals, interests and quality – especially in crisis situations.